Healing of Ocular Herpetic Disease Following Treatment With an Engineered FGF-1 Is Associated With Increased Corneal Anti-Inflammatory M2 Macrophages - Dhanushkodi, Nisha R.; Srivastava, Ruchi; Coulon, Pierre-Gregoire A.; Prakash, Swayam; Roy, Soumyabrata; Bagnol, Didier; David, Eveleth D.; BenMohamed, Lbachir (Frontiers in Immunology, 2021)
Herpes simplex virus 1 (HSV-1) infects the cornea and caused blinding ocular disease. In the present study, we evaluated whether and how a novel engineered version of fibroblast growth factor-1 (FGF-1), designated as TTHX1114, would reduce the severity of HSV-1-induced and recurrent ocular herpes in the mouse model. The efficacy of TTHX1114 against corneal keratopathy was assessed in B6 mice following corneal infection with HSV-1, strain McKrae. Starting day one post infection (PI), mice received TTHX1114 for 14 days. The severity of primary stromal keratitis and blepharitis were monitored up to 28 days PI. Inflammatory cell infiltrating infected corneas were characterized up to day 21 PI. The severity of recurrent herpetic disease was quantified in latently infected B6 mice up to 30 days post-UVB corneal exposure. The effect of TTHX1114 on M1 and M2 macrophage polarization was determined in vivo in mice and in vitro on primary human monocytes-derived macrophages. Compared to HSV-1 infected non-treated mice, the infected and TTHX1114 treated mice exhibited significant reduction of primary and recurrent stromal keratitis and blepharitis, without affecting virus corneal replication. The therapeutic effect of TTHX1114 was associated with a significant decrease in the frequency of M1 macrophages infiltrating the cornea, which expressed significantly lower levels of pro-inflammatory cytokines and chemokines. This polarization toward M2 phenotype was confirmed in vitro on human primary macrophages. This pre-clinical finding suggests use of this engineered FGF-1 as a novel immunotherapeutic regimen to reduce primary and recurrent HSV-1-induced corneal disease in the clinic.